Mechanisms and Applications of Citral's Antimicrobial Properties in Food Preservation and Pharmaceuticals Formulations - María Melissa Gutiérrez-Pacheco; Heriberto Torres-Moreno; María Liliana Flores-Lopez; Norma Velázquez Guadarrama; J. Fernando Ayala-Zavala; Luis Alberto Ortega-Ramírez; Julio César López-Romero (MDPI AG, 2023)
Citral is a monoterpene constituted by two isomers known as neral and geranial. It is present in different plant sources and recognized as safe (GRAS) by the Food and Drug Administration (FDA). In recent years, investigations have demonstrated that this compound exhibited several biological activities, such as antibacterial, antifungal, antibiofilm, antiparasitic, antiproliferative, anti-inflammatory, and antioxidant properties, by in vitro and in vivo assays. Additionally, when incorporated into different food matrices, citral can reduce the microbial load of pathogenic microorganisms and extend the shelf life. This compound has acceptable drug-likeness properties and does not present any violations of Lipinski's rules, which could be used for drug development. The above shows that citral could be a compound of interest for developing food additives to extend the shelf life of animal and vegetable origin foods and develop pharmaceutical products.